ANALISIS PEMANFAATAN, PENGAMANAN, DAN PEMELIHARAAN ASET PON XX PAPUA TAHUN 2021 - Solossa, Boaz; Kambuaya, Balthazar; Allo Layuk, Paulus K.; Salle, Hesty Theresia (Universitas Cenderawasih, 2022)
The National Sports Week held in Papua Province in 2021 is supported by the Regional Government with a budget for the construction of supporting facilities sourced from the Regional Revenue and Expenditure Budget. The management of sports facilities in the form of venues is carried out by the Department of Sports and Youth by the area management. The development, utilization and management from the beginning must have been determined by the Government so that the assets built can continue to be maintained and function. This study aims to analyze the Security, Maintenance and Utilization of PON XX Papua in accordance with Government Regulation No. 19 of 2016 concerning Management of State/Regional Property by studying the XX PON Venues located in the City & District of Jayapura. Primary data collection techniques were carried out through interviews and documentation to collect secondary data. Data analysis carried out systematically, obtained the results that all assets that had been granted to the Papua Provincial Government had been developed and utilized properly in accordance with Government Regulations.